Thermostat and equipment used to measure volume of gas (1928)
General view of the thermostat and other equipment used to measure gas volumes in order to make compressibility determinations at the High-Pressure Laboratory, part of the U.S. Department of Agriculture's Fixed Nitrogen Research Laboratory facilities located in Washington, D.C. In chemistry, compressibility refers to the measure of how much a given volume of matter decreases when placed under pressure. The Fixed Nitrogen Research Laboratory (F.N.R.L.) was established at American University in 1919 under the directorship of Arthur B. Lamb. Initially part of the War Department, the F.N.R.L. was the successor to several wartime initiatives to develop a secure domestic supply of nitrate compounds necessary for the manufacture of explosives during World War I. With a staff of about 110 individuals, including 35 to 50 chemists, the F.N.R.L. focused on the manufacture, production, and development of products of atmospheric nitrogen, including munitions and fertilizers.
Keywords: Nitrogen fertilizer industry; Nitrogen--Fixation; United States. Bureau of Chemistry and Soils; Thermostat; United States. Department of Agriculture; Scientific apparatus and instruments